Climate change effects on Antarctic benthos: a spatially explicit model approach - Torre, Luciana (2017)
The Antarctic Peninsula is one of the regions on the Earth with the clearest evidence of recent and fast air warming. This air temperature rise has caused massive glacier retreat leading to an increased influx of glacier meltwater which entails hydrological changes in coastal waters, increasing sediment input and ice-scouring impact regime. It has been hypothesized that an increase of sediment load due to glacier retreat resulted in a remarkable benthic community shift in Potter Cove, a small inlet of the South Shetland Islands. In order to test this hypothesis, we developed an explicit spatial model to explore the link between sedimentation and ice-scouring increase upon four of the most conspicuous benthic species. This is a valuable novel approach since disturbances are strongly dependent of the space. The model takes into account sediment and population dynamics with Lotka-Volterra competition, a sediment-dependent mortality term and a randomized ice-scouring biomass removal. With the developed algorithm, and using a MATLAB environment, numerical simulations for scenarios with different sedimentation and ice-impact rates were undertaken in order to evaluate the effect of this phenomenon on biological dynamics. Comparing simulation results with biological data, the model not only recreates the spatial community distribution pattern but also seems to be able to recreate the shifts in abundance under sedimentation enhancement, pointing out its importance as a structuring factor of polar benthic communities. Considering the challenges of Antarctic field work, this model represents a powerful tool for assessing, understanding, and predicting the effects of climate change on threatened Antarctic coastal ecosystems.